Comparative cost analysis of autologous peripheral blood progenitor cell and bone marrow transplantation in pediatric patients with malignancies - MG Vicent; L Madero; L Chamorro; R Madero; MA Diaz (Haematologica, 2001)
BACKGROUND AND OBJECTIVES: This study was conducted in order to compare and analyze clinical and economic outcomes of autologous transplantation using bone marrow or peripheral blood as the source of hematopoietic progenitor cells in pediatric patients with malignancies. DESIGN AND METHODS: We collected clinical information and resource utilization from 131 consecutive autologous transplantations (102 peripheral blood progenitor cell (PBPC) and 29 bone marrow (BM) transplants) at a single institution between January 1989 and December 1998 in children with a variety of malignancies. Multivariable linear regression was used to evaluate the associations between pre-transplantation variables, post-infusion events and overall costs. A cost-effectiveness analysis of transplantation for acute lymphoblastic leukemia (ALL) and acute myeloblastic leukemia (AML) patients was also performed. RESULTS: Hematopoietic recovery was faster in the PBPCT group (days to neutrophil and platelet engraftment: 9 and 13, respectively, versus 14 and 21 for BMT, p<0.0001).There were less transfusion, antibiotic and parenteral nutrition requirements and hospital stay was shorter (median 17 days; range 8-38) in the PBPCT group than in the BMT one (median 28 days; range 11-65) (p<0.0001) resulting in a median lower overall cost for PBPCT (US 7895) compared to BMT (US 11820)(p<0.0001). Major determinants of overall costs for both groups were total body irradiation (TBI)-based conditioning regimen, days of hospitalization and number of transfused platelets. In PBPCT patients, a graft containing > or = 5 x 10(6)/kg CD34+ cells decreased the total cost of transplantation by 27%. Cost-effectiveness was higher for PBPCT than BMT for pediatric AML patients (p<0.0001) whereas in ALL patients the cost-effectiveness of the two transplant strategies was not significantly different. INTERPRETATIONS AND CONCLUSIONS: We conclude that, compared to BMT, autologous PBPCT in children is associated not only with clinical benefits but also economic advantages.